The Effectiveness of Project-Based Teaching Material Development Training to Improve Teachers' Understanding in the Implementation of the Merdeka Curriculum - Reni Kusmiarti; Eli Rustinar; Yanti Paulina; Mahdijaya Mahdijaya; Bunga Darma Arumningrum (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: The Merdeka Curriculum provides freedom for teachers to choose flexible learning methods, including the use of project-based learning (PjBL). However, many teachers still face difficulties in designing project-based teaching materials that are in accordance with this curriculum.Aims: This research aims to empower Indonesian teachers in Bengkulu through project-based teaching material development training, which can improve their skills in implementing the Independent Curriculum.Methods: This service activity involved lectures, discussions, and demonstrations to 20 teachers who are members of MGMP Indonesian at SMP-MTs Bengkulu. The training is focused on the development of project-based teaching materials and their application in learning.Results: The majority of participants gave a very positive response, reaching 94.4%. Only 5.6% of participants were in a position of Doubt, and none expressed Disagree or strongly disagree. showed that the participants considered the training approach to be very relevant to the need to be able to improve understanding and skills in compiling project-based teaching materials.Conclusion: This training succeeded in empowering Indonesian teachers in Bengkulu, strengthening the implementation of the Independent Curriculum, and improving the quality of project-based learning in schools.